Ichthyoplankton composition and distribution in seascapes of equatorial atlantic - Costa, Ana Cecília Pinho (2023)
Fish eggs and larvae play key roles in nutrient and trophic cycling in oceans and their survival directly reflects on the adult stocks. Despite the importance of identifying spawning and nursery areas and seasons, few studies about them have been conducted in tropical seascapes. Ichthyoplankton sampling was carried out at 12 stations on the inner continental shelf, six located on the rhodolith bed areas and six in the seagrass meadows, with two conical nets (mouth diameter: 50 cm and mesh size: 300 μm and 200 μm). A total of 8,094 eggs and 175 larvae were collected from the seagrass meadow seascape, and 2,014 eggs and 241 larvae were collected in the rhodolith beds (SRB). The number of eggs was higher in the seagrass beds; however, the number of fish larvae was slightly higher in the SRB. Seagrass beds present less turbulent hydrodynamics and favor the retention of eggs and spawning. A more structured habitat provides better shelter, especially for larvae. However, as ontogeny progresses, the fish can explore areas with less shelter. This behavior was observed in this study, where the less structured SRB habitat had a high density of larvae in the later developmental stage. The dominance of earlier larval stages demonstrates a preference for more protected and less turbulent seascapes for nursery and offspring rearing. The results highlight that mapping of these seascapes (e.g., seagrass and rhodolith beds) will help to establish conservation measures to protect ecological connectivity and important tropical species. As for eggs, for the first time DNA barcode was used to access the diversity of fish eggs in the tropical Atlantic. 31fish eggs were successfully sequenced for the genetic analysis. One specimen was identified at order level, three at family level, 20 at genus level and seven specimens at species level. The low number of identified eggs may be related to the low number of barcoded DNAs of tropical fish deposited in databases. The results reinforce the use of DNA barcode to provide reliable data on unknown and belittled fish biodiversity in low-latitude marine areas. This approach is highly recommended for future management and the results presented can be applied in other equatorial coastal regions worldwide as long as a reliable barcode database has been developed.